Finite Element Simulation and Experimental Evaluation of Motorcycle Basket for Crashworthiness Analysis - How, Chee Keong (1999)
In this study, a detailed finite element model of a motorcycle basket used in Malaysia was developed. The model was developed specifically to address motorcycle safety issues, which had reached an alarming rate of casualties in road traffic crash. The finite element method was employed to investigate large deformation of basket at different impact speeds. The study described the simulation results of a full rigid wall impacting a basket using a non-linear finite element code, LS-DYNA Drop tests were conducted to validate and compare with the simulation results. The comparisons were made at the impact speed of 10-km/hr. Evaluation between experimental and simulation results in terms of overall impact deformation of the basket were presented. The results clearly indicate that the model correlated well with the test. Additional simulations for higher impact speeds were performed and discussed. Furthermore, simulation of a finite element model of human lower extremity striking a basket at 5O-km/hr were also addressed. The results suggest that a significant amount of energy was transformed by the leg to the basket and consequently caused the basket to deform extensively. As a result, the injury risk of the motorcyclist was minimised through absorbing most of the energy by the basket. However, further study needs to be done to improve the leg-basket model and to incorporate the model with other motorcycle structures.